p53 drives a transcriptional program that elicits a non-cell-autonomous response and alters cell state in vivo - Sydney M. Moyer; Amanda R. Wasylishen; Yuan Qi; Natalie W. Fowlkes; Xiaoping Su; Guillermina Lozano (2020)
Significance Although p53 is highly studied, the molecular and physiological consequences of the p53 transcriptional response are poorly understood. Through RNA sequencing of multiple mouse tissues upon genetic activation of p53, we identified hundreds of tissue-specific p53 target genes and a set of genes that is commonly expressed and can serve as a signature for p53 pathway activation. In the pancreas, we observed a non-cell-autonomous response while the small intestine displayed altered transcriptional cell states. Our study begins to uncover the commonalities and differences engrained in the tissue-specific and cell-specific p53 transcriptomes. Gaining a better understanding of the wild-type p53 transcriptome will subsequently lead to determining the elusive combination of genes responsible for the tumor-suppressive function of p53.